The proportion of obstetric anal sphincter injuries and associated factors among mothers who gave birth vaginally at Habru Woreda public health institutions, Amhara region, Northeast, Ethiopia, 2022 - Belyu Yehualashet Weldearegay; Simegnew Asmer Getie; Sewareg Mulu sewalem; Bizualem Tadesse Kemaw; Birhan Ambachew Taye (Elsevier, 2024)
Background: Perineal tear is a common complication of vaginal delivery. This study aimed to assess the proportion of obstetric anal sphincter injuries and associated factors among mothers who gave birth vaginally at Habru Woreda public health institutions, Amhara region, Northeast Ethiopia. Methods: A facility-based cross-sectional study was conducted from August to September 2022, with 600 participants recruited through a multi-stage sampling technique. Data were collected through interviews, observations, clinical examinations, and patient chart reviews. Multivariable regression analysis was performed to identify statistically significant variables, with an adjusted odd ratio (AOR) and 95 % confidence interval (CI) used to declare significance at p < 0.05. Findings: The proportion of obstetric anal sphincter injuries was 3.0 %(18/600), with (95 % CI: 1.7-4.3). Factors significantly associated with these injuries included antenatal care attendance (AOR: 0.13, 95 % CI: 0.03-0.47), fundal pressure (AOR: 4.71, 95 % CI: 1.29-17.10), perineal support (AOR: 0.12, 95 % CI: 0.03-0.43), head circumference ≥36 cm (AOR: 4.81, 95 % CI: 1.39-16.65), and age at marriage <18 years (AOR: 4.25, 95 % CI: 1.11-16.24). Conclusions: The proportion of obstetric anal sphincter injuries was low, and the associated factors included fundal pressure, large fetal head circumference, and early marriage, while antenatal care attendance and perineal support were protective factors. Recommendations include reducing perineal tears by supporting the perineum, avoiding fundal pressure, detecting large fetal heads early, discouraging early marriage, and promoting regular antenatal care.